White Matter Associations With Performance Validity Testing in Veterans With Mild Traumatic Brain Injury: The Utility of Biomarkers in Complicated Assessment. Issue 5 (September 2016) - Clark, Alexandra L.; Sorg, Scott F.; Schiehser, Dawn M.; Bigler, Erin D.; Bondi, Mark W.; Jacobson, Mark W.; Jak, Amy J.; Delano-Wood, Lisa
Abstract : Objective: Failure on performance validity tests (PVTs) is common in Veterans with histories of mild traumatic brain injury (mTBI), leading to questionable validity of clinical presentations. Participants: Using diffusion tensor imaging, we investigated white matter (WM) integrity and cognition in 79 Veterans with history of mTBI who passed PVTs ( n = 43; traumatic brain injury [TBI]-passed), history of mTBI who failed at least 1 PVT ( n = 13; TBI-failed), and military controls ( n = 23; MCs) with no history of TBI. Results: The TBI-failed group demonstrated significantly lower cognitive scores relative to MCs and the TBI-passed group; however, no such differences were observed between MCs and the TBI-passed group. On a global measure of WM integrity (ie, WM burden), the TBI-failed group showed more overall WM abnormalities than the other groups. However, no differences were observed between the MCs and TBI-passed group on WM burden. Interestingly, regional WM analyses revealed abnormalities in the anterior internal capsule and cingulum of both TBI subgroups relative to MCs. Moreover, compared with the TBI-passed group, the TBI-failed group demonstrated significantly decreased WM integrity in the corpus callosum. Conclusions: Findings revealed that, within our sample, WM abnormalities are evident in those who fail PVTs. This study adds to the burgeoning PVT literature by suggesting that poor PVT performance does not negate the possibility of underlying WM abnormalities in military personnel with history of mTBI.